Contribution of the GTPase Domain to the Subcellular Localization of Dynamin in the Nematode Caenorhabditis elegans - Labrousse, Arnaud M. (The American Society for Cell Biology, 1998)
Caenorhabditis elegans dynamin is expressed at high levels in neurons and at lower levels in other cell types, consistent with the important role that dynamin plays in the recycling of synaptic vesicles. Indirect immunofluorescence showed that dynamin is concentrated along the dorsal and ventral nerve cords and in the synapse-rich nerve ring. Green fluorescent protein (GFP) fused to the N terminus of dynamin is localized to synapse-rich regions. Furthermore, this chimera was detected along the apical membrane of intestinal cells, in spermathecae, and in coelomocytes. Dynamin localization was not affected by disrupting axonal transport of synaptic vesicles in the unc-104 (kinesin) mutant. To investigate the alternative mechanisms that dynamin might use for translocation to the synapse, we systematically tested the localization of different protein domains by fusion to GFP. Localization of each chimera was measured in one specific neuron, the ALM. The GTPase, a middle domain, and the putative coiled coil each contribute to synaptic localization. Surprisingly, the pleckstrin homology domain and the proline-rich domain, which are known to bind to coated-pit constituents, did not contribute to synaptic localization. The GFP-GTPase chimera was most strongly localized, although the GTPase domain has no known interactions with proteins other than with dynamin itself. Our results suggest that different dynamin domains contribute to axonal transport and the sequestration of a pool of dynamin molecules in synaptic cytosol.